GENETIC ANALYSIS OF RESISTANCE TO RICE WEEVIL ANCE TO RICE WEEVIL ANCE TO RICE WEEVIL Siltophilus Siltophilus oryzae L. IN BREAD WHEAT - AND J. P. JAISWAL, EKHLAQUE AHMAD (The Bioscan, 2018)
The present experiment was conducted at GBPUA&T, Pantnagar during 2011-12 to investigate the genetics of rice weevil resistance to wheat. The experimental materials were constituted with 15 cross combinations derived from crosses involving 3 resistant stocks and 3 highly susceptible cultivars. Almost all the scaling tests were found significant which indicated the presence of all 3 types of interactions. Six parameter models indicated the additive as well as dominance effects of genes significant in crosses obtained involving reaction types of resistant × susceptible and resistant × resistant while additive (d), dominance (h) and additive × additive (i); dominance × dominance (l) effects were found significant only in resistant × resistant crosses. In the cross K76 X K50 both the parameters i.e., h (2.383±4.102 and l (-13.700±0.936) gene effect have the opposite signs , indicating the presence of duplicate type of gene interaction, while h and l sign have the same magnitude in the cross K 21 x K 50 (2.00±2.772 and 2.667±1.012 respectively), which indicates the presence of complimentary gene effects. It may be concluded that resistance is dominant over susceptibility and is primarily governed by two genes showing inhibitory and duplicate gene action along with some minor genes